Corporate social responsibility and emerging powers. (2015) - Betz, Joachim
The growing weight of emerging powers in the world economy and their growing importance as host and also as home of transnational corporations and their affiliates has led to demands that these powers and companies take over more responsibilities in mitigating climate change and global environmental destruction as well as safeguarding or even improving social inclusion and well-being. Governments and companies in emerging economies were formerly reluctant to adopt these concepts but have more recently enacted and implemented proactive climate, environmental and more inclusive social and employment policies. Companies in emerging economies now rank nearly on par with those of advanced countries in including measures and policies for corporate social responsibility (CSR) in their business plans, but still lag in terms of concreteness of actions and in monitoring output. Causes for this policy shift are identified as well as differences in CSR performance between firms of emerging powers.